JA JA JA NEJ NEJ NEJ: Autistiskt värld- och könsgörande, affirmation, negering och förhandling - Nygren, Anna (Tidskrift för litteraturvetenskap, 2024)
YES YES YES NO NO NO: Autistic World and Gender Making, Affirmation and Neg(oti)ation Mare Kandre’s fifth novel Aliide, Aliide (1991) and Hannah Emerson’s chapbook You Are Helping This Great Universe Explode (2020) might on the surface seem to have little in common: They are written thirty years apart, in different countries (Sweden and the US) and different contexts (Kandre was at the publication of Aliide, Aliide an established and acclaimed avant-garde author whose work has since then been called gothic as well as gurlesque by contemporary Swedish critics and academics; Emerson is a nonspeaking autistic artist and poet whose poetry is being published in the context of a neurodivergent community). This article though, argues that despite their differences they are close in their way of being in the world. Emerson’s work repeats the word “yes” to create a feeling of overwhelming and exploding affirmation. In a similar way Kandre uses the repetition of the word “no” to indicate an overwhelming impossibility of being a girl. Kandre’s work has previously been analysed in line with gender and girlhood studies. Aliide, the protagonist giving name to the book, does not see herself as a “Real Girl”. Autistics have, according to the neurodiversity paradigm, been said to queer what it is to be fully human, including empathy, sense of self, how to use language, and make meaning and gender. This article investigates world making and language use in the writings of Kandre and Emerson from a queer and neuroqueer perspective. It intends not to diagnose or pathologize either Kandre or Emerson, but to read traits of neuroqueerness in their works.